Caracterização anatômica de lâminas foliares em função de doses de dejeto líquido de suíno e morfofisiologia comparada de acessos de grama-missioneira-gigante (Axonopus catharinensis Valls) - Lajús, Cristiano Reschke (2010)
This study aimed at characterizing the germplasm of axonopus catharinensis valls, in order to recommend the best accession to the continuation of studies and cultivar register, as well as characterizing the leaves of the species bromate-anatomically under distinct doses of N in pig slurry form (DLS). The trials were installed at the research center of Epagri-Cepaf, in Chapeco, Santa Catarina State, in field trials (trial I) and greenhouse trials (trial II). The trial I tested six treatments, being five doses of nitrogen (100, 200, 300, 400 e 500 kg.ha-1.year-1), in DLS form, and one additional check (absence of N + addition of P and K according to soil analysis). A completely randomized experiment design was used, with five replications. Due to the use of increasing doses of N in the form of DLS, the leaf blades of Axonopus catharinensis Valls increase the level of PB and reduce the levels of FDA, showing an improved nutritive value. The structural organization of the Axonopus catharinensis Valls is influenced by the application of increasing doses of N in the form of DLS, resulting in a smaller proportion of vascular lignified + sclerenchyma tissue and a bigger proportion of epidermic and parenchymatic tissue. In trials II, the treatments, consisting of accessions (14337, 14403, 14404, 14405 e 14406) and the age in which they would be picked (60, 90, 120, 150, 180, 210 and 240 days of growth from the transplant to the vases), were disposed in randomized blocks, with five replications. The results enabled toconclude that the accessions of Axonopus catharinensis Valls present morphophysiological differences, including the growth pattern, dry matter allocation form and phenology, making the variability in the germplasm of this hybrid evident and, therefore, the possibility of selection. The accessions 14337 and 14404 are more precocious in relation to flowering. The accessions 14337, 14403 and 14406 are the most promising for evaluations which are aimed at their register as cultivars